Quantum Learning dalam Perspektif Pendidikan Islam - Ach Zayadi (Hikmah: Journal of Islamic Studies, 2017)
The learning approach with the concept of quantum learning is a concept holding a strong philosophy that learning is a lifelong activity, which is implemented in a fun way at a class and presented with a methodology that is based on a curriculum as a blend of academic skills, physical achievements, and life skills. At a glance, this quantum approach is quite relevant to the lifelong educational philosophy that became the foundation of Islamic Education. The nature of education of Qur’an (Islam) is “rabbany” based on the first verse in the first revelation. People who carry out are also called “rabbany” who are described by al- Quran with the characteristics include teaching the book of Allah, both written (Al Qur’an) and the unwritten (the universe), and study of it continuously. This literature review will reveal another perspective on the quantum approach in optical studies of Islam. Keywords: Quantum Learning, Islamic education Pendekatan pembelajaran dengan konsep quantum learning adalah sebuah konsep yang memegang kuat falsafah bahwa belajar adalah kegiatan seumur hidup, diimplementasikan dalam kelas dengan cara yang menyenangkan, serta disajikan pula dengan metodologi yang didasarkan pada kurikulum yang merupakan perpaduan antara keterampilan akademis, prestasi fisik, dan keterampilan hidup (life skills). Sekilas pendekatan quantum ini sangatlah relevan dengan falsafah pendidikan sepanjang hayat yang menjadi pijakan dalam pendidikan Islam. Sifat pendidikan al-Qur’an (Islam) adalah “rabbany” berdasarkan ayat yang pertama dalam wahyu pertama. Orang yang melaksanakan juga disebut “rabbany” yang oleh al-Qur’an dijelaskan cirinya antara lain mengajarkan kitab Allah, baik yang tertulis (al-Qur’an) maupun yang tidak tertulis (alam raya) serta mempelajarinya secara terus menerus. Kajian literatur ini akan menguak persfektif lain tentang pendekatan quantum dalam optik kajian Islam. Kata Kunci: Quantum Learning, Pendidikan Islam